PENGARUH KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI RAWIT - Lende, Ary Prasetyo; Lano, Marten Luter; Makaborang, Marthen (Tahta Media Group, 2026)
Low-quality growing media pose a major challenge in cultivating cayenne pepper (Capsicum frutescens L.) in semi-arid areas, along with water availability. Therefore, a growing media formulation is needed to improve soil physical and chemical properties for optimal plant growth and production. This study aimed to evaluate the effects of growing media compositions consisting of alluvial soil, river sand, and rice husk charcoal on the growth and yield of cayenne pepper. The research was conducted at the Field Laboratory of the Faculty of Agricultural Technology, Artha Wacana Christian University, Kupang, from April to September 2025. The study employed a completely randomized design (CRD) with five growing media composition treatments and five replications. The treatments included P1 = 40% soil, 10% sand, 50% rice husk charcoal; P2 = 45% soil, 15% sand, 40% rice husk charcoal; P3 = 50% soil, 20% sand, 30% rice husk charcoal; P4 = 55% soil, 25% sand, 20% rice husk charcoal; and P5 = 60% soil, 30% sand, 10% rice husk charcoal. Variables observed were plant height, number of leaves, number of fruits, and total fruit weight. Data were analyzed using analysis of variance (ANOVA) followed by Duncan Multiple Range Test (DMRT) at a 5% significance level. The results indicated that differences in growing media composition significantly affected all plant growth and production variables (P < 0.05). The optimal media was treatment P5 (60% alluvial soil, 30% sand, and 10% rice husk charcoal), which yielded an average plant height of 88.90 cm, 136.20 leaves, 116.6 fruits, and a total fruit weight of 320.70 g. This study demonstrates that increasing the proportion of alluvial soil combined with sand and rice husk charcoal can enhance growing medium quality, thereby boosting the growth and yield of cayenne pepper in semi-arid environments.